Bead Characterization for Wire Based Laser Directed Energy Deposition Fabrication Process - Sidun, Muhammad Irfan Syahmi; Ishak, Ismayuzri (Jurnal Teknologi, 2023)
A three-dimensional, solid object of almost any shape or design can be created using metal additive manufacturing, often known as metal 3D printing. One of the most popular materials utilized in additive manufacturing is metal. The far more complicated procedure of directed energy deposition (DED) is frequently employed to upgrade or repair existing components. DED fabrication process will be able to construct a 3D metal object with consideration of the weld bead characteristics. Without knowing the weld bead characteristics, the mechanical integrity will not hold as the bead size is not suitable for the product. In the current study, we will study the effect of variation of parameters of the DED machine to be able to print in a continuous deposition and we will also investigate the weld bead characteristics printed by the variation of parameters with the use of DED machine. The variation of parameters of the machine are the laser power with the unit of Watt and the feedrate of the machine with the unit of mm per minute. Nine preliminary samples are printed to check whether the bead can be printed in a continuous line or not. The value of variation of parameters that bring about a continuous deposition will be jotted and continued to be taken to bead characterization for study. Six samples were printed, and the bead width and height are calculated based on the variation of parameters. Based on the result, we found that laser power will increase the bead width, but the bead height needs optimal laser power which is at 473 Watt and optimal feedrate which is on 60 mm per min to reach optimal bead height which is at 2.1162 mm. The effect of the machine feedrate on the other hand is inconsistent, thus more samples need to be gathered.